Supervisi Akademik dan Bagaimana Kinerja Guru - Hasanah, Miftahul Laili; Kristiawan, Muhammad (Tadbir : Jurnal Studi Manajemen Pendidikan, 2019)
This study aimed at investigating the implementation of academic supervision by principals, from the planning, implementation, and follow-up. Academic supervision gave impact on teachers? performance. Teachers? evaluations will be seen from the lesson plan, the implementation of instruction, assessment of learners and the follow-up. To achieve these objectives, we used quantitative approach. Data were collected through observation and questionnaires using Likert scale. The analysis used was simple regression analysis. The results showed there was significant correlation between the academic supervision by principals towards the teachers? performance. If the academic supervision increases, the teachers? performance will also increase.